Eligibility for Baroreflex Activation Therapy and medication adherence in patients with apparently resistant hypertension. Issue 7 (8th June 2021) - Schäfer, Ann‐Kathrin; Kuczera, Tim; Wurm‐Kuczera, Rebecca; Müller, Dieter; Born, Ellen; Lipphardt, Mark; Plüss, Marlene; Wallbach, Manuel; Koziolek, Michael
Abstract: Uncontrolled hypertension is a main risk factor for cardiovascular morbidity. Baroreflex activation therapy (BAT) is an effective therapy option addressing true resistant hypertension. We evaluated patients' eligibility for BAT in a staged assessment as well as adherence to antihypertensive drug therapy. Therefore, we analyzed files of 345 patients, attending the hypertension clinic at University Medicine Göttingen. Additionally, gas chromatographic‐mass spectrometric urine analyses of selected individuals were performed evaluating their adherence. Most common cause for a revoked BAT recommendation was blood pressure (BP) control by drug adjustment (54.2%). Second leading cause was presence of secondary hypertension (31.6%). Patients to whom BAT was recommended (59 (17.1%)) were significantly more often male (67.8% vs. 43.3%, P  = .0063), had a higher body mass index (31.8 ± 5.8 vs. 30.0 ± 5.7 kg/m², P  = .0436), a higher systolic office (168.7 ± 24.7 vs. 147.7 ± 24.1 mmHg, P  < .0001), and 24h ambulatory BP (155.0 ± 14.6 vs. 144.4 ± 16.8 mmHg, P  = .0031), took more antihypertensive drugs (5.8 ± 1.3 vs. 4.4 ± 1.4, P  < .0001), and suffered more often from numerous concomitant diseases. Eventually, 27 (7.8%) received a BAT system. In the toxicological analysis of 75 patients, mean adherence was 75.1%. 16 patients (21.3%) showed non‐adherence. Thus, only a small number of patients eventually received a BAT system, as treatable reasons for apparently resistant hypertension could be identified frequently. This study is—to our knowledge—the first report of a staged assessment of patients' suitability for BAT and underlines the need for a careful examination and indication. Non‐adherence was proven to be a relevant issue concerning apparently resistant hypertension and therefore non‐eligibility for interventional antihypertensive therapy. Abstract : We evaluated the eligibility for baroreflex activation therapy (BAT) of 345 patients, attending the hypertension clinic at University Medicine Göttingen. Patients' drug adherence was investigated by 75 toxicological analyses. Most common cause for a revoked BAT recommendation was blood pressure control by drug adjustment. Eventually, only less patients (7.8%) received a BAT system. Patients receiving a BAT recommendation showed specific characteristics and suffered numerous comorbidities, leading to a high cardiovascular risk, and therefore seem to greatly benefit from BAT implantation. 21.3% of patients showed non‐adherence, proving non‐adherence to be a relevant issue.